Lugar Público (1965) e a estética do Cinema Marginal - Oliveira Junior, Fernando Gleibe de (2023)
In studies on literature and cinema in Brazil, there is a special focus on Cinema Novo, a movement that intensely dialogued with Brazilian literature and brought to the screen adaptations of classic narratives from our literature, such as Vidas Secas (1938), by Graciliano Ramos, which was taken to the cinema by Nelson Pereira dos Santos. However, with regard to another group of great prominence in the history of the country's cinema, few researchers have studied the relationship between Marginal Cinema and literary narrative. In this possible approach, the figure of José Agrippino de Paula stands out, because the multi-artist has worked in cinema and literature, being the director of the impactful feature film Hitler IIIº Mundo (1968) and a writer of novels and plays. In this context, the objective of this research is to compare Lugar Público (1965), the artist's first novel, with the aesthetics of Cinema Marginal. Seeking to answer the question whether there actually existed a marginal aesthetic before Marginal Cinema, we used bibliographical research to analyze the novel and films of the movement, with the theoretical support of scholars such as Ramos (1987, 2018), Xavier (2003, 2004, 2012), Stam (1995, 2006, 2019), Robbe-Grillet (1969), Benjamin (1987) e Adorno (2003, 2009), among other relevant researchers. From the analysis, we have concluded that, even before the first film representing the aesthetics of Marginal Cinema existed, Agrippino had already created, with Lugar Público, a marginal work.